Structure and properties of steel coatings doped with aluminum - Eremin, E.N.; Yurov, V.M.; Guchenko, S.A.; Syzdykova, A.Sh. (Publishing House of the KarSU named after E.A.Buketov, 2015)
The paper presents the results of an experimental study of the structure and properties of coatings 12X18H10T + Al. Coatings were deposited in vacuum on a substrate 45 made of steel while the steel and the aluminum sputtering cathodes. The structure and properties of the coatings were investigated in an argon atmosphere, and nitrogen. An increase in the microhardness and the simultaneous reduction of friction coatings. This result has important practical significance to improve the performance of parts made of steel 45.
Keywords: structure of the coating; steel; aluminum; microhardness; friction